Collective Memory in the Age of SNS Big Data: Cultural Sensitivity, Moral Outrage, and Reputation Repair in Global Marketing - Kim, Taewan; AlHamad, Ahmad Qasim Mohammad; Kim, Tae-Kook (International Review of Management and Marketing, 2026)
This conceptual article advances a theory of collective memory violation in global marketing. It contends that certain brand crises cannot be fully understood as routine cases of value-related misconduct, creative failure, or general cultural insensitivity. Rather, these crises arise when a brand’s messaging, symbolism, timing, or product positioning intersects with socially protected memories of historical suffering, democratic movements, or shared trauma. Building on literature in collective memory, cultural trauma, moral outrage, brand crises, and crisis communication, the article introduces a five-stage process model that explains how symbolic conflict evolves into reputational delegitimation through public moral interpretation and the amplification of outrage. It further proposes a typology of memory-related brand crises and outlines memory-sensitive recovery strategies that go beyond conventional apology-based responses. The Starbucks Korea “5.18 Tank Day” controversy is used as the central illustrative case, demonstrating how a global brand can provoke moral outrage by inadvertently activating nationally institutionalized remembrance through seemingly commercial communication. The article contributes to international marketing by framing historical memory as a legitimacy system relevant to markets, to crisis communication by identifying conditions under which standard response strategies fall short, and to managerial practice by providing a checklist for anticipatory screening, symbolic withdrawal, and culturally grounded repair in sensitive contexts.